Perinatal outcome in adolescent pregnancy: a retrospective study at Karnali Academy of Health Sciences - Kayastha, Nirajana; Shrestha, Sandeep; Sindan, Namrata (Journal of Chitwan Medical College, 2021)
Background: Adolescent pregnancy is a multifactorial social and global health problem, especially in remote, rural setting in low-middle-income countries. This study was conducted to determine the perinatal outcome of adolescent pregnancy of this region. Methods: A retrospective study was conducted in Karnali Academy of Health Sciences (KAHS), Jumla among nulliparous pregnant adolescent women aged 15 to 19 years (n=363) and those aged 20 to 24 years (n=445) who delivered in this hospital from April 2017 to April 2020 AD. Maternal and perinatal characteristics were compared between these groups. The categorical data between adolescent and adult women were compared. Chi-square test, Odds ratio and 95% confidence interval were examined using SPSS version 16. Results: During the study period, the incidence of adolescent pregnancy was 22%. The adolescent mothers had significantly higher incidence of anemia (p=0.005, OR:2.7; 95% CI:1.34-5.78), abnormal fetal presentation (p=0.006, OR:3.1; 95%CI:1.38-7.31) and preterm deliveries (p value<0.0001, OR:3.47; 95% CI:1.94-6.19). Regarding perinatal outcome, low birth weight (LBW) babies (p=0.02, OR:1.56; 95% CI:1.07-2.29), lower mean birth weight (2715+/-586 grams) and early neonatal deaths (NNDs) (p=0.02, OR:2.52; 95% CI:1.12-5.69) were significantly associated with adolescent mothers. There was a higher proportion of neonatal admission in adolescent group compared to adult group (p=0.0006, OR:2.18; 95% CI:1.39-3.40). Conclusions: Adolescent pregnancy is associated with increased risk of anemia, preterm delivery, low birth weight, early neonatal deaths and neonatal admissions. Targeted interventions from the community to health care level are important to decrease the adverse perinatal outcome of adolescent pregnancy.